2021
DOI: 10.5603/ep.a2021.0075
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with acromegaly receiving lanreotide autogel: a real-world observational study

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Endokrynologia Polska" are listed in PubMed. The final version may contain major or minor changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Noteworthy, controversial results have been reported, since the poor quality of life seen at diagnosis of acromegaly has been demonstrated either to persist despite long-term remission regardless of the treatment used to achieve biochemical control (109)(110)(111)(112)(113), or to improve after GH and IGF-I normalization (114)(115)(116). Lower AcroQol scores have been reported in patients with long disease duration (109,112), multiple comorbidities (117) and in women (118).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, controversial results have been reported, since the poor quality of life seen at diagnosis of acromegaly has been demonstrated either to persist despite long-term remission regardless of the treatment used to achieve biochemical control (109)(110)(111)(112)(113), or to improve after GH and IGF-I normalization (114)(115)(116). Lower AcroQol scores have been reported in patients with long disease duration (109,112), multiple comorbidities (117) and in women (118).…”
Section: Discussionmentioning
confidence: 99%
“…Applying disease-specific instruments to evaluate the quality of life in a specific patient population is of significant advantage as these instruments measure aspects specific to the population in question. Previous studies indicated quality of life is impaired in patients with acromegaly [ 30 , 31 ]. However, it remains stable after administration of somatostatin analogues [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated quality of life is impaired in patients with acromegaly [ 30 , 31 ]. However, it remains stable after administration of somatostatin analogues [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly (AG) is a rare disease caused by excessive production of the growth hormone (GH) and insulin-like growth factor 1 (IGF1) ( 12 ). In more than 90% of cases, the disorder stems from a GH-secreting pituitary adenoma ( 13 , 14 ), and as a consequence, patients present with somatic growth, metabolic dysfunctions ( 15 , 16 ), and a decreased quality of life ( 17 ). The stimulatory effect of GH on the mammalian erythropoiesis in vitro has been widely recognized ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%